1987
DOI: 10.1177/030006058701500609
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with 0.05% Halometasone/1% Triclosan Cream in the Treatment of Acute Infected and Infection-Prone Eczema in Egypt

Abstract: This is a report of a non-comparative trial to assess the usefulness of a 0.05% halometasone and 1% triclosan combination in a cream base in the treatment of acute infected and infection-prone eczematous skin disorders. The trial was carried out in three centres. Of the 126 patients admitted to the trial, 25 were lost to follow-up. The remaining 101 patients utilized the cream as the only treatment during the 3-week duration of therapy. Medication was applied to the lesions twice daily without occlusive dressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Earlier studies have shown that combination of halometasone and antibacterial agents/fusidic acid is safe and effective in the treatment of eczema. [11-12] Studies have shown that combination of halometasone and fusidic acid is safe and effective[19] and our study confirms this in Indian population. This FDC was well tolerated among our patients, as only one AE was reported in the group A.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Earlier studies have shown that combination of halometasone and antibacterial agents/fusidic acid is safe and effective in the treatment of eczema. [11-12] Studies have shown that combination of halometasone and fusidic acid is safe and effective[19] and our study confirms this in Indian population. This FDC was well tolerated among our patients, as only one AE was reported in the group A.…”
Section: Discussionsupporting
confidence: 85%
“…[9] Treatment with halometasone and antibacterial agent (triclosan) was found to be superior with higher success and cure rate along with good safety profile; an early cure (in less than 20 days) compared to other steroid and antibiotic combination. [10–12] Safety, efficacy, and tolerability of Halometasone in Indian patients with acute and chronic eczema have been documented. [13]…”
Section: Introductionmentioning
confidence: 99%